2006
DOI: 10.1038/sj.bjc.6603082
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor β and neoadjuvant therapy with tamoxifen: prediction of response and effects of treatment

Abstract: In order to elucidate the relative importance of oestrogen receptor (ER)a, ERb and an ERb variant (ERb2/bcx) in the response of breast cancers to tamoxifen, tumour levels of each receptor were assessed in 36 patients before and after 3 months of neoadjuvant treatment with tamoxifen (20 mg daily). All patients were postmenopausal women presenting with large ERa-positive breast cancers. Clinical response to treatment was assessed by tumour volume changes as determined from sequential ultrasounds and pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 44 publications
2
37
0
1
Order By: Relevance
“…We found fifteen studies investigating ERβ expression and response to endocrine therapy. Of these, thirteen examined ERβ protein expression using primarily IHC [82,86,87,93,94,97,104,105,107,[111][112][113][114]. Only three of these studies [82,97,107] separate ERβ tumor populations based on ERα status, although the majority of tumors typically contain both subtypes.…”
Section: Clinical Correlations Between Erβ Expression and Response Tomentioning
confidence: 99%
See 3 more Smart Citations
“…We found fifteen studies investigating ERβ expression and response to endocrine therapy. Of these, thirteen examined ERβ protein expression using primarily IHC [82,86,87,93,94,97,104,105,107,[111][112][113][114]. Only three of these studies [82,97,107] separate ERβ tumor populations based on ERα status, although the majority of tumors typically contain both subtypes.…”
Section: Clinical Correlations Between Erβ Expression and Response Tomentioning
confidence: 99%
“…Of the thirteen studies examining ERβ protein expression (Table 1), one reported no significant correlation between ERβ levels and the response to TAM therapy in ERα+ only tumors [111]. Another group looked exclusively at ERα− tumors from patients treated with hormonal therapy, chemotherapy, or radiotherapy, either alone or in combination [87].…”
Section: Clinical Correlations Between Erβ Expression and Response Tomentioning
confidence: 99%
See 2 more Smart Citations
“…Rody and colleagues observed in a neoadjuvant study that Her-2 seems to be highly predictive for chemotherapy outcome (24). Concerning ERß Miller and colleagues focused on ERß expression with neoadjuvant tamoxifen therapy and observed a decrease of ERß1 (28). Possible effects of aromatase inhibitors or chemotherapy on ERß or a possible predictive value of ERß for cytotoxic drugs remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%